ESP Learners’ Attitudes Towards the Moodle Virtual Learning Environment (LITPAM, 2024)
The incorporation of technology plays a key role in teaching and learning language skills. The integration of technology provides several opportunities for both language learners and teachers such as providing an inclusive learning environment, enabling learners to have access to various resources, and practicing language in a different way. This research investigates the attitudes of ESP learners in the context of maritime English through Moodle virtual learning platform. The study analyzes three factors such as the customization of Moodle platform to meet learners’ needs as ESP learners, critical skills development of learners, and how this platform enhances interaction among learners. A questionnaire was used by the researcher to gather data from the participants using a quantitative approach. The results showed that Moodle has great potential for customization of ESP sources due to its various features and learners can easily have access to the course contents and ESP teachers can design their courses on this platform effectively. The findings of the study also showed that learners could improve their critical thing when dealing with the course content. The platform also provides high interaction among leaners and learners with teacher. Nevertheless, educators and instructional designers must consider time constraints, inadequate resources, technical difficulties, and unfamiliarity with the platform. These findings present valuable perspectives for improving ESP courses that fulfill student needs and transform their perspectives on education.